UWAGI O FILOZOFII MITU JOSEPHA CAMPBELLA - Korczak, Andrzej (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Андрей Корчак. Заметки о философии мифа Джозефа Кемпбелла. Проведен анализ взглядовДжозефа Кемпбелла относительно символов и мифов. Согласно этому ученому есть две основных ошиб-ки в интерпретации мифов в Западной культуре. Первая ошибка состоит в буквальной интерпретациимифа, а вторая, в рассмотрении мифа как будто бы это было описание метафизической действительности. Согласно нему миф, символ – никогда не есть описанием превосходства, но только указанием наэто. Автор показывает как Кемпбелл интерпретирует Христианские символы, как например, рождениесына Бога девственницей, Смертью и Воскресеньем Христа, также как и падения Адама и Евы от библейской книги происхождения. Я подаю отношение ученого к рассмотрению различных интерпретациймифа – биологический и психоаналитический. Влияние Индусской мистики играет большую роль в этихинтерпретациях, хотя ученый был хорошо осведомлен о Европейской мистике, к которой он также часто обращается. По мнению Джозефа Кемпбелла, самая глубокая тайна мифов – единство жизни, скрытой за множественностью явлений. Он солидаризировал это единство с превосходством или духом. Автор пытается также показать как преимущества, так и недостатки такой интерпретации символов и мифов.Andrey Korchak. Notes about philosophy of myth of Joseph Kempbell. I introduce the view of JosephCampbell regarding the symbols and myths. According to this scholar there are two basic mistakes in the interpretationof the myths in the Western culture. The first mistake consists in literal interpretation of the myth, andthe second one in treating the myth as if it was a description of a metaphysical reality. According to him themyth… the symbol is never a description of transcendence but only an indication of it. I demonstrate how Campbellinterprets the Christian symbols, such as the birth of the son of God by a virgin, the Death and the Resurrectionof Christ, as well as the fall of Adam and Eve from the biblical book of genesis. I present the relation of thescholar to the various interpretations of the myth – the biological and the psychoanalytical. The influences of theHindu mysticism play a great role in these interpretations, although the scholar is well knowledgeable of theEuropean mysticism to which he also frequently refers. In the opinion of Joseph Campbell the deepest secret ofthe myths is the oneness of life hidden behind the plurality of the phenomena. He identifies this oneness with thetranscendence or the spirit. I try to show both the advantages and the disadvantages of such interpretation of thesymbols and myths.Кeywords: myth, symbols, interpretations of myth, interpretations of symbols.